Pengaruh Self Awareness dan Organizational Citizenship Behavior pada Kinerja Karyawan yang Dimoderasi Efektivitas Organisasi - Lia Meidiana Putri; Lukiyana Lukiyana (Journal of Management and Business Review, 2023)
In the era of scientific and economic development, the need for individual transportation administration continues to grow. All aspects of the company including HR are required to work harder in developing achievements. This research aims to know the effect of self awareness OCB or organizational citizenship behavior, employee performance on organizational effectiveness. The independent variables in this study consisted of (X1) self awareness, (X2) organizational citizenship behavior, the independent variable namely (Y) employee performance, with the moderator variable namely (Z) organizational effectiveness. The purpose of this research is to determine the effect of self awareness and OCB on employee performance moderated by organizational effectiveness at PT. Indofood CBP Sukses Makmur Tbk. The population in this research are employees of PT. Indofood CBP Sukses Makmur Tbk in South Jakarta as many as 100 respondents as samples in the study. Primary data is the type of data that uses a questionnaire by one hundred respondents who are filled in directly, the data obtained is processed using Partial Least Square (PLS). The research data shows that self awareness has a positive and significant effect on employee performance, OCB also has a positive and significant effect on employee performance, organizational effectiveness has a positive and significant influence on employee performance, the moderating influence of organizational effectiveness has no effect on it but weakens the effect of self awareness and OCB on employee performance.